URGENSI KETERLIBATAN ORANG TUA DALAM PEMBELAJARAN DARING ANAK DITINJAU DARI FILSAFAT PENDIDIKAN ANAK IBNU SINA - Yetty Faridatul Ulfah; Oong Ridhoi; S Sridadi (MAMBA'UL 'ULUM, 2022)
This policy of limited face-to-face meetings (PTM) indicates that 50% of students have been allowed to study in schools, while the rest still hold learning at home. Thus, the presence of parents in assisting children's education is very important, especially when learning online at home during the covid 19 pandemic. Social mobility, increasing and enriching scientific information are very necessary for parents because they assist their children for 24 hours in educating and teaching science and morals. This research applied library research. Secondary data was a data collection technique used in this study classified indirectly to the object of study. Secondary data sources were obtained from national and international journals related to distance learning during the covid-19 pandemic and children's moral education according to Ibnu Sina. Technique of data analysis was carried out through four stages encompassing data collection, reduction, presentation, and conclusions. According to Ibnu Sina’s perspective in educating children, parents must understand the purpose of educating children, the children's education curriculum, children's learning processes, children's learning methods. If the sequence is understood and done as well as possible, it will be easy to educate and teach children in any condition, including during covid pandemic period.